Composition of Shark Catches With Conservation Status in Mukomuko District, Bengkulu - Panji Anugrah Ramadhan; Mulyono Baskoro; Wazir Mawardi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
Mukomuko Regency is one of Bengkulu Province's regencies with abundant marine resources. It has a fishing port, one of which is the Ipuh sub-district fishing port and the Teramangjaya sub-district fishing port. This study aimed to determine the size, length, weight, and composition of shark species landed at the Mukomuko Regency fishing port to identify the types of sharks that are protected based on the IUCN conservation status and the suitability of shark catches. The survey method was used to visit the research location at the ship's landing port, measure the length and weight of the sharks, and take pictures of them. The results of the sharks obtained were two species of sharks, namely the kejen shark (Loxodon Macrorhinus) with a status of almost threatened NT, 35 were found, and the Hammerhead Shark (Sphyrna lewini) with a status of very threatened CR, 15 were found. Of all the types of sharks caught, they were still juveniles and not yet suitable for catch.